Optimization of chitosan and sodium carboxymethylcellulose as mucoadhesive system in theophylline tablet - Irawan, Eka Deddy; ., Farhana (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
Mucoadhesive tablet for asthma treatment were prepared by mixing theophylline with two variations of polymers. The purpose of this research was to controlled drug release from the dosage form. Theophylline mucoadhesive tablets were prepared by direct compression using chitosan and sodium carboxymethylcellulose as mucoadhesive polymers. Mucoadhesive strength measured using rabbit gastric mucosa and in vitro drug dissolution was subjected in a hydroclorid acid buffer pH 1.2 for 10 hours. The optimized formula was obtained by analyzing both evaluation using factorial design. Formula with 5.4 % of chitosan and 14.5 % of sodium carboxymethylcellulose followed zero order kinetics. The optimized formulation showed by 8.38-10.91% of chitosan and 28.84-29.09% of sodium carboxymethylcellulose with mucoadhesive strength between 25-40 gram and 43.5%-55% drug was released in 10 hours.Key words: Mucoadhesive, chitosan, CMC Na, E, factorial design.